Analisis Kandungan Senyawa Bioaktif, Nutrisi dan Aktivitas Antioksidan pada Minuman Ekstrak Beras Hitam - Dina Fitriyah; Dessya Putri Ayu; Surya Dewi Puspita; Yohan Yuanta; Mohammad Ubaidillah (Puslitbang Sinergis Asa Professional, 2021)
Black rice contains high bioactive compounds that have antioxidant activity so that it has the potential as a source of functional food that can help to overcome various health problems. Black rice extract has high potential to be developed into an antioxidant beverage. Research on the content of bioactive compounds, antioxidant activity, and nutrients in black rice extract beverages has not been widely studied in Indonesia. The objective of this study was to determine the content of bioactive compounds, activity, and nutrients of black rice extract. Four types of commercial black rice grains were extracted using methanol as comparison (without treatment) and using water with a temperature of 90°C for 15 and 25 minutes, with the ratio of water: rice powder (20, 25 and 30 ml/ g). The black rice extracts were tested for total phenolic compound, antioxidant activity, protein, and iron content. The highest total phenolic content, flavonoids, and antioxidant activity of black rice extract beverages were 4.54 mg GAE/g (water ratio: rice powder 20 ml/g, 15 minutes), 14.51 mg QE/g (water ratio: rice powder 20 ml/g, 15 minutes), and 73.44% (water ratio: rice powder 30 ml/g, 15 minutes). The total protein and iron content of extract black rice beverage was 0.3115- 0.3620% and 0.0100- 0.0123%, respectively. The presence of high content of bioactive compounds, protein, iron, and antioxidant activity in black rice extract with a processing time of 15 and 25 minutes at 90°C, and the ratio of water: rice powder (20, 25, 30 ml/g) indicates that the processing conditions can provide a reference in producing black rice extract beverages which are rich in bioactive compounds, antioxidants, and nutrients. The presence of iron in brown rice extract may help overcome iron deficiency.